NiMn layered double hydroxides derived multiphase Mn-doped Ni sulfides with reduced graphene oxide composites as anode materials with superior cycling stability for sodium ion batteries - Chen, Jingwei (2020)
Sodium ion batteries have been drawing attention in recent years as the next generation batteries, due to the even distribution and abundance of sodium source. Metal sulfides as the promising sodium ion battery anode materials have the advantages of relatively high electronic conductivity than the metal oxides and high theoretical capacity. However, the accompanied severe volume changes upon de/sodiation often lead to fast capacity decay, poor rate capability and unsatisfactory cycling stability. In our work, multiphase Mn-doped Ni sulfides (NMS) nanoparticles were obtained by sulfidation process, the NMS nanoparticles deliver higher electronic conductivity and larger sodium diffusion coefficient than the multiphase Ni sulfides (NS) nanoparticles, resulting in a better rate performance. With the addition of reduced graphene oxide (rGO), NMS nanoparticles anchored on the surface of reduced graphene oxide (NMGS) were obtained. The optimized NMGS can deliver specific capacity of 460.9 mAh/g at a current density of 50 mA/g, while retaining a capacity of 169.4 mAh/g at an increased current density of 5000 mA/g, demonstrating good rate performance. In addition, when the ether-based electrolyte (1 M NaCF3SO3 in diethylene glycol dimethyl ether) is used, the NMGS can maintain a capacity of 229.2 mAh/g at high current density of 5000 mA/g, and retain capacity of 206.1 mAh/g at 500 mA/g after 2000 cycles. The high specific capacity, great rate performance with excellent cycling stability emphasizes the promising potential of NMGS as sodium ion battery anodes.